2021
DOI: 10.2147/jmdh.s326209
|View full text |Cite|
|
Sign up to set email alerts
|

Unmet Healthcare Needs Among Elderly Malaysians

Abstract: Purpose: Older people often have chronic diseases which require a continuity of care over the long term. Countries undergoing population aging need to ensure that older people are receiving the care they need. This study assesses the prevalence of, reasons for, and factors associated with unmet healthcare needs among older people individuals in Malaysia. Patients and Methods: This cross-sectional study used data collected during 2018-2020 from 1204 older adults aged 60 and older selected from Selangor state, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Among South Korean adults aged 65 years and older, the group with depression was 1.45 times more likely to have unmet healthcare needs than those without depression [ 17 ]. Gao et al found that middle-aged and older adults in China having depressive symptoms had increased odds of having unmet healthcare needs [ 19 ] and the same were found among older Malaysian adults [ 18 ]. Only a few studies investigated the association between unmet medical service needs and depression, and there is a lack of these studies in European countries’ settings.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Among South Korean adults aged 65 years and older, the group with depression was 1.45 times more likely to have unmet healthcare needs than those without depression [ 17 ]. Gao et al found that middle-aged and older adults in China having depressive symptoms had increased odds of having unmet healthcare needs [ 19 ] and the same were found among older Malaysian adults [ 18 ]. Only a few studies investigated the association between unmet medical service needs and depression, and there is a lack of these studies in European countries’ settings.…”
Section: Introductionmentioning
confidence: 98%
“…Unmet healthcare needs can be defined as not receiving an appropriate level of care for the area of significant difficulties [ 12 ]. However, in older adult studies unmet healthcare needs are measured in significantly different ways, with some studies measuring a wide range of unmet needs in environmental, physical, psychological, and social areas of functioning [ 12 , 13 , 14 , 15 ], while others measured a more specific inability to use needed medical services [ 16 , 17 , 18 , 19 ]. Across international surveys and studies of unmet needs of older adults, the cost of the services or the financial situation emerged as one of the most common reasons for unmet healthcare needs [ 17 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to the pandemic, research has found interconnections between depression, anxiety and unmet healthcare needs. Multiple studies have found that experiencing symptoms of depression is associated with elevated unmet needs and vice versa [13][14][15][16]. In a crosssectional study of 845 older adults in Germany, the odds of experiencing depressive symptoms were 82% higher in the group that had unmet needs [17].…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have found an association between mental disorders and unmet need for mental health care. Available evidence indicates that experiencing symptoms of depression is associated with high unmet needs for care and vice versa (Park et al, 2017;Jung & Ha, 2021;Shah et al, 2021;Zhou et al, 2021). In a study among German adults, Stein et al (2019) reported that the odds of experiencing depressive symptoms were 82% higher in the group that had unmet needs.…”
Section: Prevalence Of Depression Based On Severitymentioning
confidence: 99%